Field days as approach towards capacity building and transfer of technology - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
During the field visits, participants (usually pilot growers) were provided with technical backstopping and information on specific technologies and management practices